Technologický postup výroby ocelových konstrukcí - Vedra, Jakub (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Tato diplomová práce se zabývá legislativou a kontrolou výroby ocelových konstrukcí výrobků. Hlavním cílem diplomové práce je vypracování potřebných technických předpisů a dokumentů, které zajišťují splnění technických požadavků k výrobě ocelových konstrukcí výrobků a jsou v souladu s legislativními předpisy a technickými normami.

This thesis deals with the legislation and control the production of steel constructions. The main aim of thesis is to develop the necessary technical regulations and documents to ensure compliance with technical requirements for the manufacture of steel constructions which are in accordance with legislative regulations and technical standards.
Technological production processing of steel construction
Keywords: ocelová konstrukce; norma; legislativa; svařování; jakost; kontrola; steel construction; standard; legislative; welding; quality; inspection